The Relationship Between Gender and Hypertension Severity in the Working Area of Puskesmas Cempaka Putih, Banjarmasin - Tasalim, Rian (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Hypertension is a global health issue, increasing morbidity and mortality due to cardiovascular complications. Gender differences affect blood pressure regulation, with men generally having higher blood pressure before menopause, while postmenopausal women face a greater risk due to hormonal changes. However, research on gender and hypertension severity remains inconclusive in Indonesia. This study aims to analyze the relationship between gender and hypertension severity at Puskesmas Cempaka Putih, Banjarmasin. Method: This cross-sectional study used a quantitative approach. A total of 68 hypertensive patients were selected through purposive sampling. Blood pressure was measured using a sphygmomanometer, while secondary data were obtained from medical records. The Chi-Square test was used to assess the relationship between gender and hypertension severity. Result: Among respondents, 38.2% were men and 61.8% were women. Of the men, 65.4% had Grade 1 hypertension, while 34.6% had Grade 2 hypertension. Among women, 50% had Grade 1 hypertension, and 50% had Grade 2 hypertension. The Chi-Square test yielded p = 0.214, indicating no significant association between gender and hypertension severity. Conclusion: Although gender differences in hypertension severity were observed, no significant correlation was found. Other factors, such as lifestyle and adherence to antihypertensive treatment, may play a more significant role. Future research with a larger sample and additional variables is recommended to further investigate gender differences in hypertension severity.